Review article: towards a considered and ethical approach to organ support in critically‐ill patients with cirrhosis. Issue 2 (16th November 2012) - Berry, P. A.; Thomson, S. J.; Rahman, T. M.; Ala, A.
Summary: Background: Increasing numbers of patients are being admitted to hospital with decompensated chronic liver disease in the UK. A significant proportion will develop complicating extra‐hepatic organ dysfunction, but the selection of those who should be admitted to intensive care is complex and challenging. Alcohol‐related liver disease also presents complex ethical dilemmas. Aim: To review recent survival analyses and explore differences in secondary and tertiary care; to highlight strengths and weaknesses of prognostic models, therapeutic advances and shifts in prognostic expectation. We also aim to explore the ethical challenges presented by addiction and self‐injury in an area of limited resource. Methods: We searched PubMed for articles discussing 'cirrhosis', 'prognosis', 'critical illness', 'organ failure', 'renal failure', 'alcohol', 'ethics' and 'addiction'. We also explored particular ethical dilemmas encountered by the authors and colleagues. Results: Prognosis has improved in many cirrhotic complications and historically poor outcomes in tertiary care may reflect a more complex patient cohort. Previously 'untreatable' complications are now being managed successfully. Estimates of survival are more accurate after a 48‐h period of supportive care. Physicians are not best placed to make judgments with regard to deservingness, moral responsibility, rationing and access to organ support in cases of acute deterioration related to alcoholism, and the case for denying support must be made on purely medical grounds. Conclusions: An early, aggressive approach to organ support is justified. Further discussions between hepatologists and critical care physicians are required to determine acceptable burden‐to‐benefit ratios for prolonged intensive care support in young alcoholic patients.